Effectiveness of glucocorticoids in preventing esophageal stricture and predictors of stricture after esophageal ESD: 5 years of experience in a single medical center - Wang, Qingxia; Ding, Yuan; Qian, Qiliu; Zhu, Yinnan; Shi, Ruihua (Frontiers in Medicine, 2025)
BackgroundEsophageal stricture is one of the major complications after endoscopic submucosal dissection (ESD) of the esophagus. However, even with steroid prophylaxis, stenosis still occurs in up to 45% of patients. Accordingly, the aim of this study was to evaluate the efficacy and safety of steroid therapy in preventing esophageal strictures after ESD, as well as to assess the predictors of esophageal strictures after the application of steroids.MethodsBetween February 2018 and March 2023, 207 patients who underwent esophageal ESD at Southeast University Affiliated Zhongda Hospital were retrospectively enrolled. We evaluated stenosis rate, number of endoscopic dilations after ESD, the interval between the first endoscopic dilatation after ESD and explored risk factors for strictures after steroid prophylaxis.ResultsIn the control group, the oral steroids group, and the combined group, the stenosis rates were 83/87 (95.4%), 44/53 (83.0%), and 56/67 (83.6%), respectively; the number of endoscopic dilations were 3.43 (±2.22), 2.34 (±2.17), and 1.52 (±1.25), respectively; the time intervals between first endoscopic dilation and ESD procedure were 38.36 (±6.87), 68.18 (±9.49), and 96.82 (±8.41) days, respectively; all these indicators were significantly better in the oral and combined groups than in the control group (p < 0.05). Multivariate analysis identified lesion circumference ≥ 5/6th and submucosal injection of solution were two independent factors on esophageal stricture formation (p < 0.05).ConclusionSteroid prophylaxis is effective and safe in preventing esophageal stenosis. Moreover, lesion circumference and submucosal injection of sodium hyaluronate were two independent factors on esophageal stricture formation even with steroids administration.